2010
DOI: 10.1016/j.actbio.2010.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of bone defect healing using a new biocomposite scaffold: An in vivo study in sheep

Abstract: a b s t r a c tPrevious studies support resorbable biocomposites made of poly(L-lactic acid) (PLA) and b-tricalcium phosphate (TCP) produced by supercritical gas foaming as a suitable scaffold for tissue engineering. The present study was undertaken to demonstrate the biocompatibility and osteoconductive properties of such a scaffold in a large animal cancellous bone model. The biocomposite (PLA/TCP) was compared with a currently used b-TCP bone substitute (ChronOS™, Dr. Robert Mathys Foundation), representing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 30 publications
3
41
0
3
Order By: Relevance
“…X-ray micro-computed tomography (lCT) was also used for systematic morphological characterization of selected foams [12,[43][44][45][46]. The measurements were performed using a Skyscan 1076 micro-CT scanner (Skyscan).…”
Section: Methodsmentioning
confidence: 99%
“…X-ray micro-computed tomography (lCT) was also used for systematic morphological characterization of selected foams [12,[43][44][45][46]. The measurements were performed using a Skyscan 1076 micro-CT scanner (Skyscan).…”
Section: Methodsmentioning
confidence: 99%
“…makes the composite material brittle and thus, less resistant to deformation. 29 Our results showed that PLA/30 nβ-TCP and PLA/10 nβ-TCP scaffolds exhibited better mechanical properties than PLA/50 nβ-TCP scaffolds.…”
Section: Resultsmentioning
confidence: 51%
“…The biodegradation of PLA in vivo and in vitro have been verified in various studies. [19][20][21] EC is a cellulose-based material and can be degraded by enzymes and bacteria. [22][23][24] EC has been used widely as a coating material for drugs.…”
Section: Discussionmentioning
confidence: 99%